2003
DOI: 10.1183/09031936.03.00039503
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic dead space in face masks used with noninvasive ventilators: a lung model study

Abstract: The aim of this study was to determine what the influence of different designs of face masks and different noninvasive ventilator modes would be upon total dynamic dead space.Using a spontaneous breathing model, total dynamic dead space was measured when using 19 commercially available face masks and a range of ventilators in various ventilation modes.Total dynamic dead space during spontaneous ventilation was increased above physiological dead space from 32% to 42% of tidal volume by using face masks. The use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
50
0
7

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(59 citation statements)
references
References 11 publications
2
50
0
7
Order By: Relevance
“…While confirming the results previously obtained by Saatchi et al [5] using a different technique, the study by Fodil et al [6] extends the analysis to the helmet, an interface that, despite increasing popularity because of its excellent tolerability over time [7], still raises concern because of the high risk of re-breathing related to its large internal volume. Fodil et al [6] elegantly show that when the internal volume is much larger than the tidal volume, as occurs with the helmet, the importance of the convective flows is negligible and is only minimally affected by the breathing cycle.…”
supporting
confidence: 83%
See 1 more Smart Citation
“…While confirming the results previously obtained by Saatchi et al [5] using a different technique, the study by Fodil et al [6] extends the analysis to the helmet, an interface that, despite increasing popularity because of its excellent tolerability over time [7], still raises concern because of the high risk of re-breathing related to its large internal volume. Fodil et al [6] elegantly show that when the internal volume is much larger than the tidal volume, as occurs with the helmet, the importance of the convective flows is negligible and is only minimally affected by the breathing cycle.…”
supporting
confidence: 83%
“…This notion has been repeatedly challenged by physiological and clinical studies. In a bench investigation, Saatci et al [5] found that the increase in the actual dead space observed during spontaneous unassisted breathing consequent to the application of oro-nasal masks was reduced close to zero thanks to the continuous flow produced by turbine ventilators throughout expiration.…”
mentioning
confidence: 99%
“…18 Nonetheless, for a respiratory rate of 20 breaths/min, this adds about 2 L/min of dead space. Saatci et al 19 found that a face mask increased dynamic dead space from 32% to 42% of tidal volume. The use of PEEP also reduces the effective dead space of the mask.…”
Section: The Interface and Asynchronymentioning
confidence: 99%
“…The use of PEEP also reduces the effective dead space of the mask. 19 For ventilator/interface combinations that use a leak port, CO 2 can be cleared from the mask by incorporating the leak port into the mask rather than the circuit. This effectively reduces the dead space of the mask.…”
Section: The Interface and Asynchronymentioning
confidence: 99%
See 1 more Smart Citation